Demonstration of a state of light with purely transverse angular momentum - Banzer, Peter; Neugebauer, Martin; Aiello, Andrea; Marquardt, Christoph; Lindlein, Norbert; Bauer, Thomas; Leuchs, Gerd (Optics InfoBase Conference Papers, 2013)
We demonstrate and discuss a state of light with purely transverse angular momentum - a photonic wheel - generated by tight focusing of polarization tailored light. We use an experimental nanoprobing technique to measure the corresponding distribution.
CRIS-Team Scopus Importer:2022-06-05

Experimental demonstration of the geometric spin hall effect of light in highly focused vector beams - Neugebauer, Martin; Banzer, Peter; Bauer, Thomas; Lindlein, Norbert; Aiello, Andrea; Marquardt, Christoph; Korger, Jan; Leuchs, Gerd (Quantum Electronics and Laser Science Conference, QELS 2012, 2012)
We demonstrate the geometric spin Hall effect of light by focusing a specially polarization tailored beam of light, resulting in the generation of purely transverse angular momentum in the focal plane. © 2012 OS

Geometric spin Hall effect of light in tightly focused polarization-tailored light beams - Neugebauer, Martin; Banzer, Peter; Bauer, Thomas; Orlovas, Sergejus; Lindlein, Norbert; Aiello, Andrea; Leuchs, Gerd (Physical Review A - Atomic, Molecular, and Optical Physics, 2014)

Long distance free-space propagation of light carrying orbital angular momentum - Lavery, Martin P.J.; Peuntinger, Christian; Günthner, Kevin; Bauer, Thomas; Banzer, Peter; Elser, Dominique Alexander; Boyd, Robert W.; Padgett, Miles J.; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2016)
We present analysis of the technical challenges facing deployment of longdistance free-space links employing orbital angular momentum multiplexing. Our analysis indicates atmospheric mitigation techniques, and modal purity are important consideration for system design.
CRIS-Team Scopus Importer:2022-06-05

Multi-twist polarization ribbon topologies in highly-confined optical fields - Bauer, Thomas; Banzer, Peter; Bouchard, Frederic; Orlov, Sergej; Marrucci, Lorenzo; Santamato, Enrico; Boyd, Robert W.; Karimi, Ebrahim; Leuchs, Gerd (New Journal of Physics, 2019)
Electromagnetic plane waves, solutions to Maxwell's equations, are said to be 'transverse' in vacuum. Namely, the waves' oscillatory electric and magnetic fields are confined within a plane transverse to the waves' propagation direction. Under tight-focusing conditions however, the field can exhibit longitudinal electric or magnetic components, transverse spin angular momentum, or non-trivial topologies such as Mobius strips. Here, we show that when a suitably spatially structured beam is tightly focused, a three-dimensional polarization topology in the form of a ribbon with two full twists appears in the focal volume. We study experimentally the stability and dynamics of the observed polarization ribbon by exploring its topological structure for various radii upon focusing and for different propagation planes.
CRIS-Team WoS Importer:2019-05-24

The photonic wheel - demonstration of a state of light with purely transverse angular momentum - Banzer, Peter; Neugebauer, Martin; Aiello, Andrea; Marquardt, Christoph; Lindlein, Norbert; Bauer, Thomas; Leuchs, Gerd (Journal of the European Optical Society: Rapid Publications, 2013)